Effect of Intravenous Ethanol on Capsaicin‐Induced Hyperalgesia in Human Subjects. (24th May 2016) - Arout, Caroline A.; Perrino, Albert C.; Ralevski, Elizabeth; Acampora, Gregory; Koretski, Julia; Limoncelli, Diana; Newcomb, Jenelle; Petrakis, Ismene L.
Abstract : Background: The objective of this study was to assess ethanol's (EtOH's) effects on capsaicin‐induced hyperalgesia in healthy participants. Specifically, we investigated the change in area of capsaicin‐induced hyperalgesia following 3 interventions: intravenous EtOH at 2 targeted breath alcohol concentrations (BrAC), or placebo. Methods: Eighteen participants participated in 3 test days in a randomized order. Each test day, participants received an intradermal capsaicin injection on the volar surface of the forearm, followed by either infusion of high concentration EtOH (targeted BrAC = 0.100 g/dl), low concentration EtOH (targeted BrAC = 0.040 g/dl), or placebo. The area of hyperalgesia was determined by von Frey technique at 2 time points, prior to EtOH infusion, and again when target BrAC was reached. The primary outcome was the percent change in the area of capsaicin‐induced hyperalgesia. Additional outcome measures included the visual analogue scale of mood states (VAS), which was administered at each time point. Results: There was a marked 30% reduction in the area of capsaicin‐induced hyperalgesia with infusion of a high concentration of EtOH ( p < 0.05). Low concentration EtOH produced a 10% reduction in hyperalgesia area, although this finding did not reach significance. Further, participants reported significant feelings of euphoria and drowsiness at high concentrations of EtOH ( p < 0.05), as measured by the VAS. Conclusions: In a human model examining pain phenomena related to central sensitization, this study is the first to demonstrate that capsaicin‐induced hyperalgesia is markedly attenuated by EtOH. The capsaicin experimental pain paradigm employed provides a novel approach to evaluate EtOH's effects on pain processing. The antihyperalgesic effects of EtOH observed have important clinical implications for the converging fields of substance abuse and pain medicine and may inform why patients with chronic pain often report alcohol use as a form of self‐medication. Abstract : This study assessed ethanol's effects on capsaicin‐induced hyperalgesia in healthy participants. We investigated change in area of capsaicin induced hyperalgesia following placebo, low, or high intravenous ethanol infusion (confirmed by breath alcohol concentration [BrAC]). There was a 30% reduction in the area of hyperalgesia following high BrAC ethanol (* p < 0.05). Low BrAC ethanol produced a 10% reduction in hyperalgesic area. This study is the first to demonstrate that capsaicin‐induced hyperalgesia is markedly attenuated by ethanol.